2014
DOI: 10.4012/dmj.2014-121
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-structural evaluation of an anodic oxidated titanium dental implant

Abstract: Anodic oxidation is used for the surface treatment of commercial implants to improve their functional properties for clinical success. Here we conducted ultrastructural and chemical investigations into the micro-and nanostructure of the anodic oxide film of a titanium implant. The anodic oxidized layer of a Ti6Al4V alloy implant was examined ultrastructurally by transmission electron microscopy (TEM) and scanning electron microscopy (SEM). They were also analyzed using energy dispersive X-ray spectrometry (EDS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…Pores in anodic oxide films result from dielectric breakdown of the oxide layer during the anodization process with higher applied voltages yielding larger pores . The chemistry of the treated surface in our study consisted of titanium oxides of low crystallinity with incorporated phosphate ions concentrated in the outer surface with near depletion of the aluminum and vanadium alloying elements . In the control implants, the oxide layer was a mere 4 nm in thickness, which is typical of commercially prepared titanium and titanium alloy components that have been cleaned and passivated in nitric acid in the conventional manner .…”
Section: Discussionmentioning
confidence: 99%
“…Pores in anodic oxide films result from dielectric breakdown of the oxide layer during the anodization process with higher applied voltages yielding larger pores . The chemistry of the treated surface in our study consisted of titanium oxides of low crystallinity with incorporated phosphate ions concentrated in the outer surface with near depletion of the aluminum and vanadium alloying elements . In the control implants, the oxide layer was a mere 4 nm in thickness, which is typical of commercially prepared titanium and titanium alloy components that have been cleaned and passivated in nitric acid in the conventional manner .…”
Section: Discussionmentioning
confidence: 99%
“…One factor that may have influenced these results is the use of an intermediate Ti6Al4V abutment that was anodized as a surface treatment. Yamagami et al [7] analyzed the nanostructure and the atomic composition of the anodized Ti6Al4V alloy and observed that aluminum and vanadium were not present on the outermost surface of the anodic oxide layer. This could explain why the groups that interposed the anodized abutment (E2 and E4) presented a lower release of ions.…”
Section: Discussionmentioning
confidence: 99%
“…Titanium and its alloys are highly used materials because of their biocompatibility, good mechanical properties, resistance to corrosion [5][6][7] and ability to osseointegrate into the body [5]. However, in the oral environment, biodegradation occurs due to the thermal, microbiological and enzymatic conditions therein [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the anodizing process modifies the amorphous oxide film in a layer of crystalline oxide on the implant surface [ 8 ]. Current techniques that obtained a layer of crystalline and uniform oxide, showed improvements in the results in this layer when compared to that formed naturally, in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%